Investigating information needs of library users : a case of Bushbuckridge Community Library - Sambo, Precious Kholomile (My University, 2018)
The purpose of this research is to investigate the information needs of rural communities in Bushbuckridge. Investing information of communities is vital because information plays an important role in enabling communities to meet their development needs, such as employment, education, health, safety, food security, and leisure. Libraries are therefore instrumental in helping library users to meet these needs. The study utilised triangulated (quantitative) and (qualitative) research methods. Participants in this study included 100 library users, four librarians and one library manager drawn from four local libraries through a combination of random (probability) and purposive (non-probability) sampling. The quantitative part of the study i.e. survey measured the perceptions of users on library services through questionnaires, while unstructured interviews elicited the experiences of librarians in addressing the information needs of library users in the four libraries of Bushbuckridge. Findings from the survey revealed, inter alia, that: most (65%) users had access to library services, although high travelling costs were a major barrier for those living in remote villages; a large number of users (60%) still depended on librarians to help them find information, while a growing number of users (33% had begun using computers and the internet to meet their information needs; the most important reasons for using the library were: assignments, study and careers, and, the majority of users in all four libraries were generally satisfied with the quality of the services rendered, although significant improvements were required in the supply of materials and water. Findings from interviews with librarians demonstrated that significant steps had been taken to address information needs of users across the four libraries. Common examples include: books and materials; computers and internet services; study groups; user training, and outreach programmes – although these were hampered by shortage of staff and vehicles. Cross-cutting problems included delays in purchasing of library materials; shortage of water and low perceptions about the benefits of library services in the community. In light of these results, it was concluded that information needs of library users had been partially met, with greater room for improvement in areas like human resources, information technology, transport and procurement systems and processes. The research findings have demonstrated that if provided well, library information services may help reduce the challenges of illiteracy, poverty and unemployment in this area. In light of these findings, the study recommended, inter alia, that the skills of library staff along with procurement systems and processes be upgraded in order to satisfy the information needs of library users in the study area. The study further recommended that outreach programmes be scaled up to increase awareness in the community about the role and benefits of library services in facilitating community development, particularly in Bushbuckridge where challenges of illiteracy, poverty and unemployment continue unabated.
Thesis (M. INF.) --University of Limpopo, 2018
Keywords: Information needs; Rural communities; Library users; Libraries and the poor; Library catalogs and users; Library resources